SGIP1 alters internalization and modulates signaling of activated cannabinoid receptor 1 in a biased manner - Hájková, Alena; Techlovská, Šárka; Dvořáková, Michaela; Chambers, Jayne Nicole; Kumpošt, Jiří; Hubálková, Pavla; Prezeau, Laurent; Blahos, Jaroslav (Neuropharmacology, 2016)
Many diseases of the nervous system are accompanied by alterations in synaptic functions. Synaptic plasticity mediated by the endogenous cannabinoid system involves the activation of the cannabinoid receptor 1 (CB1R). The principles of CB1R signaling must be understood in detail for its therapeutic exploration. We detected the Src homology 3-domain growth factor receptor-bound 2-like (endophilin) interacting protein 1 (SGIP1) as a novel CB1R partner. SGIP1 is functionally linked to clathrin-mediated endocytosis and its overexpression in animals leads to an energy regulation imbalance resulting in obesity. We report that SGIP1 prevents the endocytosis of activated CB1R and that it alters signaling via the CB1R in a biased manner. CB1R mediated G-protein activation is selectively influenced by SGIP1, β-arrestin associated signaling is changed profoundly, most likely as a consequence of the prevention of the receptor's internalization elicited by SGIP1.
Keywords: Receptor, Cannabinoid, CB1; beta arrestin 2; myši; Two-Hybrid System Techniques; Cell Membrane; lidé; Brain; Humans; potkani Wistar; Mice; Animals; Endocytosis; Saccharomyces cerevisiae; zvířata; HEK293 buňky; Carrier Proteins; MAP Kinase Signaling System; Transfection; mozek; neurony; endocytóza; beta-Arrestin 2; techniky dvojhybridového systému; Rats, Wistar; transfekce; buněčná membrána; MAP kinasový signální systém; Neurons; transportní proteiny; HEK293 Cells; receptor kanabinoidní CB1